Introducing The Minnesota Multiphasic Personality Inventory-Adolescent-Restructured Form (MMPI-ARF) - Robert P. Archer (European Scientific Journal, ESJ, 2016)
This paper presents information on the development and structure of the MMPI-A-RF, a 241-item self-report inventory designed to evaluate adolescent psychopathology in clinical, forensic, educational, and medical settings. The MMPI-A-RF as a revision of the MMPI-A, which is the most popular test of adolescent psychopathology in the United States. The MMPIA-RF is scheduled to be released in the first half of 2016 by the University of Minnesota Press, and distributed by Pearson Assessment.